Factors, Issues, and Problems in the Recruitment and Retention of Teachers for Rural Schools - Vernon J. Storey (Journal of Research in Rural Education, 1993)
I report the findings ofa survey of558 teachers in ruralschools and districts throughout BritishColumbia, Canada. The study sought demographic data; background information about influences on subjects' decisions to enter, to remain in, or to leave their districts; and data regarding their participation in a government loan forgiveness program. Theprimaryaimof the research wastodevelop aprofile oftheruralschool teacher andhis/hercareer decision patterns, in order to extend and strengthen both the current literature and school districts' recruitment and retention efforts. The data were gathered by means of a survey questionnaire, tabulated, and analyzed for significant differences among various demographic groups. Sher's (983) categories-characteristics, conditions, and compensation-provided the framework for the discussion of the findings. Thestudy yieldeda comprehensive demographic profile of ruralschool teachers. Further, thedata indicated that the jobitself, lifestyle, school district recruiters, the financial dimension, social and recreational opportunities, and partner's job wereimportant factors in at leastoneof teachers', three sets of majorcareer decisions.